Application of Information Services to Develop Understanding of Students' Attitudes towards Students' Free Sex Behavior at Harapan Mekar High School Medan - Kesuma, Eza Pauza; Muharmi, Tetty (Indonesian Journal Education, 2022)
The object of study in this study was to find out the application of information services in developing students' understanding of attitudes toward free sex behavior in Class X-IPA SMA Harapan Mekar Medan. This research is qualitative research. Data collection methods used in this study were observation, interviews and documentation. The subjects of this study were students of Class X-IPA SMA Harapan Mekar Medan. Based on the results of the information service data, it can develop an understanding of the dangers of free sex behavior in X-IPA class students, considering that at the age of their youth, students still find it difficult to control themselves. Therefore, to overcome this, special and in-depth attention is needed through information services. As a result, after the implementation of these services, students (counselee) experience positive changes as expected